La responsabilité des centres d'arbitrage - Elatafy, Sherif (Université Jean Moulin Lyon 3, 2016)
Les litigants sollicitent les centres d’arbitrage pour diriger l’arbitrage dans toutes ses phases afin de donner une garantie supplémentaire qui assure la validité de la sentence arbitrale. Compte tenu du rôle important que les centres d’arbitrage jouent pendant l’instance arbitrale, les litigants mécontents de la sentence arbitrale ou du jugement annulant la sentence tentent d’engager la responsabilité du centre d’arbitrage dès lors qu’il a surveillé, dirigé et participé au rendu de la sentence.De plus en plus la responsabilité des centres d’arbitrage est mise en cause devant les juridictions étatiques différentes, les fonctions et les pouvoirs exercés par les centres d’arbitrage ainsi que le régime de responsabilité leur est applicable font l’objet d’une attention critique de la part de la doctrine dans plusieurs systèmes juridiques. On s’interroge sur l’origine des rapports qui lient les centres d’arbitrage aux autres acteurs de l’arbitrage, sur les obligations et les pouvoirs conférés aux centres d’arbitrage, et sur les fonctions exercées par les centres d’arbitrage pour établir enfin un régime de responsabilité homogène et pertinent à l’égard des fonctions exercées par les centres d’arbitrage qui a une vocation à s’appliquer dans la majorité des systèmes juridiques. Parties to arbitration seek arbitral institutions to administrate their arbitration in order to have an extra guarantee that ensures the validity of the arbitral award. Given the role that arbitral institutions play during the arbitral procedure, parties unsatisfied either by the arbitral award or the annulment of the award tend to claim the liability of arbitral institution for the awards it had supervised, administered and participated in.The more the allegations of liability raise against the arbitral institutions before courts, the more the issue of arbitral institutions’ functions, powers and liability becomes controversial in different jurisdictions. Therefore, the present study tends to clarify the origin of the relationship existing between arbitral institutions and other parties involved in the arbitration at issue, the duties and powers assigned to the arbitral institutions and the functions performed by the arbitral intuitions, which helps eventually in establishing a kind of liability that complies with the functions performed by the arbitral institutions and can be applied in many jurisdictions.
Keywords: Acte juridictionnel; Administrative functions; Agreement to administrate an arbitration; Approbation; Arbitrage; Arbitrage commercial international; Arbitrage institutionnel; Arbitragem; Arbitral Awards; Arbitral institutions; Arbitration; Business contract; Centre d'arbitrage; Challenging arbitrator; Civil liability; Clause exclusive de responsabilité; Condition excluding liability; Consensual protection; Contrat de direction d’arbitrage; Contrat d’entreprise; Décision institutionnelle; Examen prima facie; Faute intentionnelle; Faute lourde; Fonctions administratives; Fonctions juridictionnelles; Forum; Gross negligence; Immunity; Immunité; Institutional arbitration; Institutional decision; Judicial conduct; Judicial functions; Prima facie examination; Protection conventionnelle; Responsabilité civile; Récusation d’arbitre; Sentence arbitrale; Willful misconduct